Blossom-End Clearing of Grapefruit - Mark A. Ritenour; Huating Dou; Ed Etxeberria (EDIS, 2003)
Blossom-end clearing (BEC) is characterized by the translucent, watersoaked appearance of the fruit peel (most commonly at the blossom end) caused by internal bruising and juice leakage from juice vesicles. Juice vesicles in the bruised areas usually have a gray tinge compared with unbruised tissue, and BEC-affected fruit develop off flavors. BEC is visible within 24 hours after bruising (often much earlier) and can affect up to 90% of the fruit in some loads. Decay, in particular mold, often develops in areas with BEC symptoms. BEC has also been referred as “wet bottoms,” “stylar-end clearing,” “water bottom,” “waterlog,” and “wet wick.” This document is HS937, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2003.